Low percolation threshold and electromagnetic shielding effectiveness of nano-structured carbon based ethylene methyl acrylate nanocomposites. (15th June 2017) - Mondal, Subhadip; Ganguly, Sayan; Das, Poushali; Khastgir, Dipak; Das, Narayan Ch
Abstract: In the present work, we developed industrially scalable and affordable Ketjen carbon black (K-CB)-ethylene methyl acrylate copolymer (EMA) composites with low percolation threshold and efficient electromagnetic interference (EMI) shielding efficiency associated with high potential of absorption dominance of electromagnetic (EM) radiations by conductive dissipation. The dispersion and distribution of K-CB inside the EMA elastomer have been affirmed with the help of qualitative electron micrograph techniques. The EMA matrix and K-CB filler interactions have been corroborated through bound rubber content and dynamic mechanical properties. Interfacial interactions between K-CB and polymer matrix are pivotal in determining the good reinforcing efficiency with tunable electrical conductivity as well as adjustable EMI shielding ability in K-CB filled composites. The proposed composites lead to a low percolation threshold (8.6 wt%) and promising high EMI shielding value of 33.9 dB for 20 wt% K-CB in the X-band frequency as compared to other expensive carbon fillers. On account of the thorough analysis of the composites, our high hopes have been placed on the promotion of low budget and flexible EMA/K-CB composite for the emerging field of superior EMI shielding applications. Graphical abstract: EMI shielding and conduction mechanism of the EMA/K-CB composites.